Genome-Wide Transcriptome Analysis of Cadmium Stress in Rice. (29th February 2016) - Oono, Youko; Yazawa, Takayuki; Kanamori, Hiroyuki; Sasaki, Harumi; Mori, Satomi; Handa, Hirokazu; Matsumoto, Takashi
Abstract : Rice growth is severely affected by toxic concentrations of the nonessential heavy metal cadmium (Cd). To elucidate the molecular basis of the response to Cd stress, we performed mRNA sequencing of rice following our previous study on exposure to high concentrations of Cd (Oono et al., 2014). In this study, rice plants were hydroponically treated with low concentrations of Cd and approximately 211 million sequence reads were mapped onto the IRGSP-1.0 reference rice genome sequence. Many genes, including some identified under high Cd concentration exposure in our previous study, were found to be responsive to low Cd exposure, with an average of about 11, 000 transcripts from each condition. However, genes expressed constitutively across the developmental course responded only slightly to low Cd concentrations, in contrast to their clear response to high Cd concentration, which causes fatal damage to rice seedlings according to phenotypic changes. The expression of metal ion transporter genes tended to correlate with Cd concentration, suggesting the potential of the RNA-Seq strategy to reveal novel Cd-responsive transporters by analyzing gene expression under different Cd concentrations. This study could help to develop novel strategies for improving tolerance to Cd exposure in rice and other cereal crops.